2010
DOI: 10.1007/s00394-010-0127-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, double-blind and placebo-controlled study using new probiotic lactobacilli for strengthening the body immune defence against viral infections

Abstract: In conclusion, intake of the probiotic strains Lactobacillus plantarum HEAL 9 (DSM 15312) and Lactobacillus paracasei 8700:2 (DSM 13434) reduces the risk of acquiring common cold infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 15 publications
7
95
0
3
Order By: Relevance
“…Furthermore, a randomized, parallel, double-blind, placebo-controlled study showed that consumption of L. plantarum HEAL 9 and L. paracasei 8700 : 2 for a 12-week period could reduce the risk of acquiring common cold infections in healthy individuals. For example, the incidence of acquiring one or more common cold episodes, the number of days with common cold symptoms, and pharyngeal symptoms were all reduced [27]. …”
Section: Probiotics For Immune Disease Prevention and Treatmentmentioning
confidence: 99%
“…Furthermore, a randomized, parallel, double-blind, placebo-controlled study showed that consumption of L. plantarum HEAL 9 and L. paracasei 8700 : 2 for a 12-week period could reduce the risk of acquiring common cold infections in healthy individuals. For example, the incidence of acquiring one or more common cold episodes, the number of days with common cold symptoms, and pharyngeal symptoms were all reduced [27]. …”
Section: Probiotics For Immune Disease Prevention and Treatmentmentioning
confidence: 99%
“…In this study the great amount of inflammatory cytokine RNA for IFN-γ, IL1β and IL17 has been obtained after 6 weeks, though in the LP+HP group (LP+HP=normal chow diet with 400μl of viable cells of L. plantarum ZDY 2013), the increase in the level of mRNA which is related to IL1β and IFN-γ has been stopped. It can be inferred from this research that L. plantarum ZDY 2013 pretreatment could prevent Th1 cell response by H. pylori infection [6].…”
Section: The Role Of L Plantarum Zdy 2013 and L Fermentum Uco-979c mentioning
confidence: 68%
“…Looking at the data from single studies, a daily supplementation of probiotics (mainly lactobacilli and bifidobacteria) showed a slight effect on ARI in adults, elderly, and selected at-risk populations (table 2). However, either a combined probiotic preparation (including L. gasseri, B. longum, and B. bifidum) or a symbiotic formulation (including L. rhamnosus, L. plantarum, and B. lactis) demonstrated, in randomized controlled trials, a good efficacy in shortening the duration of episodes by about 2 days and the severity of symptoms [22][23][24].…”
Section: Prevention Of Respiratory Infections In the Adult Populationmentioning
confidence: 99%